Synthesis of the oxazolidinone fragment of thelepamide. Issue 7 (3rd April 2022) - Ashida, Naoki; Ida, Kousuke; Koide, Yumi; Vavricka, Christopher J.; Izumi, Minoru; Kiyota, Hiromasa
Abstract: Thelepamide, an unique ketide-amino acid isolated from a marine annelid worm Thelepus crispus, has a unique oxazolidinone ring derived from cysteine, glycine and valine. Rareness in nature as well as promising bioactive possibility make the oxazolidinone ring an attractive synthetic target. The hydroxy oxazolidinone fragment of thelepamide was prepared by acid-catalysed N, O -acetal formation between a ketoamide and formaldehyde. Lactone-carbonyl selective isopropyl addition to an oxazilidine–dione under Grignard conditions also forms the target compound. Graphical Abstract: